The Effect of Information Technology Infrastructure and the Internet of Things on Defense Industry Management Information Systems - Wasserbauer, Michal (Dinasti International Journal of Digital Business Management, 2022)
The article Literature Review the Effect of Information Technology Infrastructure and the Internet of Things on Defense Industry Management Information Systems is a literature review scientific article. The purpose of this article is to build a hypothesis of the influence or role between variables that will be used in future research, within the scope of management information systems science. The method of writing articles is a library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are: 1) Information technology infrastructure affects the defense industry management information system partially; 2) The Internet of things affects the defense industry management information system partially; and 3) Information technology infrastructure and the internet of things have a partial effect on the defense industry management information system. Apart from these 2 exogen variables that affect the endogenous variables of the defense industry driver's license, there are still other factors including employee capability, encryption and employee education.